Autoclaving and Alkaline Hydrolysis Effects on the Particle Size and Solubility of Grouper (Epinephelus sp.) Nano-calcium Powder in In Vitro Gastrointestinal Tract Simulation - Pipin Kusumawati; Priyanto Triwitono; Sri Anggrahini; Yudi Pranoto (Jurnal Ilmiah Perikanan dan Kelautan, 2022)
Highlight Research Autoclaving for 3x3 hours followed by alkaline hydrolysis (3x3AH) may lower nano-calcium particle size into 47.47 nm 3x3AH sample contain 30.73% calcium and 18.37% phosphorus 3x3AH sample created the best calcium solubility (26.14 %) in comparison to synthesized CaCO3 (14.34 %) Grouper nano-calcium powder includes trace quantities of organic content, such as protein and fat, which enhance calcium's solubility.   Abstract Fish bone nano-calcium production may solve two challenges, providing calcium for lactose-intolerant people and recycling bone waste. Fish bone autoclaving prior to extraction reduces fat, denatures collagen, and softens bones but only few researches have compared autoclaving duration with nano-calcium product quality, particle size, and its solubility in in vitro testing. This study studied the influence of autoclaving duration followed by alkaline hydrolysis on nano-calcium characteristics to enhance calcium solubility in in vitro gastrointestinal simulation experiments. The dried grouper (Epinephelus sp.) bone was divided into four groups: 0A (no autoclaving), 3A (3 h autoclaving), 2x3A (double cycle for 3 h autoclaving), and 3x3A (triple cycle for 3 h autoclaving). Each group was followed by alkaline hydrolysis, designated as 0AH, 3AH, 2x3AH, and 3x3AH. The results showed that autoclaving for 3x3 hours followed by alkaline hydrolysis resulted in lowest nano-calcium particle size of 47.47 nm consisting of 30.73% calcium and 18.37% phosphorous. 3x3AH sample created the best calcium solubility (26.14%) in comparison to synthesized CaCO3 (14.34%). In contrast to synthetic CaCO3, grouper nano-calcium powder includes trace quantities of organic contents, such as protein and fat, which enhance calcium solubility. In vivo research should be established to study the bioavailability and influence of grouper nano-calcium powder on bone density.